CORRELATION OF FNAC AND HISTOLOGICAL DIAGNOSIS IN THE EVALUATION OF BREAST LUMPS - Shazia Aslam; Sadia Hameed (Journal of University Medical & Dental College, 1970)
ABSTRACT Objective: To correlate the cytological findings of breast lumps with their histomorphological diagnosis on excision. Materials and methods: This comparative study was conducted in the Department of Pathology, University Medical and Dental College, Faisalabad from September 2008 to December 2011. All women who had a clinically palpable breast lump were subjected to fine needle aspiration cytology (FNAC) which was followed by an excision biopsy. Results: Fifty six patients who presented with a breast lump in the surgical and gynecological department at Madina Teaching Hospital were referred to the Pathology Department for FNAC. Thirty one were reported as C2 lesions, 1 was reported as C3, 1 as C4 and 23 cases were reported as C5 lesions. On histopathological examination, out of 31 cases which were reported as C2 lesions, 30 were benign while 1 case turned out to be medullary carcinoma of the breast (false negative). The case which was reported as C3 turned out to be a benign lesion-giant fibroadenoma-on histopathology. The case which was diagnosed as C4 lesion turned out to be carcinoma on histopathology. All the 23 cases which were diagnosed as C5 lesion on FNAC proved to be malignant on histopathology. Conclusion: Breast cytology is an effective and rapid method of diagnosis of breast diseases. It helps in deciding which patient needs an early open biopsy.